Fabrication of an amine-modified ZIF-8@GO membrane for high-efficiency adsorption of copper ions. (21st March 2019) - Wei, Ning; Zheng, Xudong; Ou, Hongxiang; Yu, Peilin; Li, Qiao; Feng, Shanshan
Abstract : Metal–organic framework (MOF) materials are a class of hybrid organic–inorganic supramolecular materials. Abstract : Metal–organic framework (MOF) materials are a class of hybrid organic–inorganic supramolecular materials. Owing to their highest specific surface area, lowest crystal density and adjustable pore size and functional structure, MOF materials have the potential for some special applications in the field of adsorption of heavy metal contaminants. However, it is difficult to collect and reuse them in adsorption separation because of their nanometer size. Therefore, graphene oxide (GO) with good film-forming properties is used. In this paper, an f-ZIF-8@GO composite membrane material was developed by using GO and a zeolitic imidazolate framework (ZIF-8) material and was modified with 3-aminopropyl-triethoxysilane (APTES) by amine functionalization. After a series of structural characterizations, it was applied to the adsorption of copper ions in water and its adsorption properties were tested. The results showed that the adsorption capacity at pH = 6.0 was the largest, and an increase in temperature was not conducive to the adsorption reaction. The adsorption data were fitted to the Freundlich equation and the quasi-second order kinetic equation. The adsorption of Cu 2+ on water was multilayer, and the equilibrium adsorption capacity was up to 1872.24 mg g −1 . The prepared materials exhibited high selectivity to copper ions; they could be reused as adsorbents for many times and maintained high adsorption capacity. This kind of material is of great significance for the adsorption and separation of heavy metal ions in water.